Bangladesh : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper on Bangladesh reviews institutional developments in the foreign exchange market since 2002. In 2002, there have been several aspects of the financial system and exchange market in Bangladesh that posed impediments to a floating exchange rate system. The financial system has been dominated by state-owned commercial banks with assets amounting to about 24 percent of GDP and accounting for some 46 percent of industry net assets. Market interventions have been largely confined to building foreign exchange reserves and to countering rare disorderly market conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet